Unusual presentation of ileal intussusception due to submucosal lipoma in a child and its management - Nisha Girish; Naveen Thomas; Gayathri Natraj; K V Satish Kumar; Neena John (Wolters Kluwer Medknow Publications, 2023)
Idiopathic intussusception is the most common form of intussusception in infants and young children. In older children and adults, intussusception being rare, the lead point is usually an underlying bowel pathology (Meckel's diverticulum, hemangioma, carcinoids, polyps, submucous lipomas, etc.) and these are called pathological lead points (PLP's). The management of an obese child with recurrent abdominal pain for over 2 years, diagnosed with ileo-ileal intussusception due to submucosal lipoma is reported here.